PENGEMBANGAN MEDIA PROMOSI KESEHATAN BUKU DIARY MENGENAI PENCEGAHAN ANEMIA PADA REMAJA PUTRI DI SMAN 1 CIPARAY (Politeknik Kesehatan Kemenkes Bandung, 2023)
Background: Anemia is a health problem that is often experienced by young women because adolescents are in a period of growth that requires higher nutrients, including iron. anemia in adolescent girls, namely stunted growth, decreased endurance, decreased body fitness, and decreased activity and learning achievement due to lack of concentration. The development of diary media as health information is needed to provide health information to young women. Purpose: promotion of health promotion media diary book about anemia prevention in adolescent girls at SMAN 1 Ciparay. Methods: This study uses the PPE development model according to Richey and Klein, namely Planning (planning), Production (production), and Evaluation (evaluation). The number of samples was 38 students using proportional stratified random sampling technique. Results: Based on the results of the exploration of the need for health promotion media diaries, diaries on anemia prevention became an attractive medium for young women by paying attention to media design starting from media content, color themes and pictures/illustrations. Making a prototype of the diary media which was formed based on the 3 stages of the PPE development model (Planning, Production and Evaluation). The results of the media according to the material in accordance with 80%, the media according to 90.8% and the media according to the users 95.9% so that it can be considered very feasible. Recommendation: This research should be able to conduct further tests to determine the effectiveness or effect of using a diary on the prevention of anemia in adolescent girls.